Experimental and numerical investigation on the optical and thermal performance of solar parabolic dish and corrugated spiral cavity receiver. (1st May 2017) - Pavlovic, Sasa; Daabo, Ahmed M.; Bellos, Evangelos; Stefanovic, Velimir; Mahmoud, Saad; Al-Dadah, Raya K.
Abstract: A low cost solar collector with a dish reflector and spiral absorber is examined in this work. This collector is investigated experimentally and numerically with a developed thermal model in the Engineering Equation Solver (EES). Numerical simulations are performed by the commercial software OptisWorks. The solar ray distribution inside these receiver geometries, including the helical coil used for the heat transfer fluid, was determined using this tool. The final results show that the thermal performance is about 34%, due to the high rate of thermal losses. After validating the numerical model, it is used for investigating the collector for various operating conditions. Three working fluids (Water, Therminol VP-1 and Air) are compared energetically and exergetically for various combinations of volumetric flow rates and operational temperature levels. The results proved that water is the most appropriate working fluid, among those investigated, as it is able to efficiently work at low temperature levels, while the thermal oil is the best at higher temperature values, according to thermal analysis. The exergetic analysis showed that air is the best choice in low temperatures and thermal oil in greater temperatures. Finally, an open receiver of a conical cavity shape with a helical tube was optically investigated, as a second strategy for enhancing the optical performance of the receiver. The results show that an average flux value of about 2.6 × 10 5 W/m 2 was absorbed by the helical conical shape with an aperture area of 0.01606 m 2 . Highlights: Experimental testing of solar prototyping solar dish collector was conducted. Thermal and exergetic efficiencies of the different working fluids were determined. A numerical model was used for estimating the energetic and exergetic performance. The effect of the conical receiver position on optical efficiency was investigated.